Determinação da presença de microplásticos em diferentes estruturas de solo: produto de compostagem, agregado de solo urbano e sedimentos - Tefa, Febriana Marcela Amaral (Universidade Federal de São Carlos, 2026)
Microplastics (MPs) are persistent and widely distributed environmental contaminants, whose presence has been increasingly recorded in terrestrial environments. This study aimed to determine the occurrence, distribution, and characterization of MPs in different compartments of the terrestrial environment, including compost products, urban soil aggregates, and coastal sediments. To this end, density separation, organic matter digestion, and visual characterization techniques were used to identify the particles in terms of abundance, shape, color, and size. The results showed the presence of MPs in all compartments analyzed. In compost products, MPs were identified in both the pre- and post maturation stages, at a ratio of 3933 MPs/kg, with a predominance of fibers and wide morphological diversity, indicating that the composting process is not capable of completely eliminating these contaminants. In urban soil aggregates, we obtained an abundance corresponding to 10,283 MPs/kg, with a higher concentration of MPs in water-stable aggregates, especially in the larger fractions, suggesting direct interaction of these contaminants with the soil structure and possible influence on its stability. In coastal sediments, MPs showed variable distribution along the vertical profile, with an average of 11,594.67 ± 9,227.647 MPs/kg, reinforcing the role of sediments as compartments for accumulation and environmental recording of contamination. The results demonstrate that MPs are widely distributed in terrestrial systems, highlighting the need for effective waste management and plastic contamination mitigation strategies.
Determination of the presence of microplastics in different soil matrices: compost, urban soil aggregate, and sediments
Keywords: microplásticos; compostagem; solo urbano; agregados do solo; sedimentos; microplastics; composting; urban soil; soil aggregates; sediments; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::QUIMICA DO SOLO; 6. Água Potável e Saneamento